APPLICATION OF LEAN METHODOLOGY PRESCRIPTION OF NUTRITION SUPPLEMENTS ASMEDICATION BY DIETITIANS - J Woods; M.A. Silvers; R. Raja; A.M. Gordon; M.K. Inkstera; J. McDonald (The Korean Society of Nephrology, 2012)
In a major Victorian hospital, dietitians observed that requests tomedical staff to prescribe nutritional supplements via themedication chart were inefficient. This led to delays in the deliveryof nutritional recommendations, thus compromising patients'nutritional status. Lean Methodology was applied to simplify theordering of patients' nutritional supplements as medication(NSAM) by dietitians. A literature review was conducted. Directobservation and value stream mapping were used to identifyprocess time and wasted time related to NSAM prescription. Adetailed root cause analysis of identified issues was undertaken,followed by the development of an implementation plan. Thefollowing problems were identified: ordering process wascomplicated and not linear, delay in patient receiving NSAM (2.8days, range 0-23 days), and 60% repeat requests by the dietitian forNSAM. An implementation plan was developed which included:submission to the Medical Executive Committee to seekprescribing privileges for dietitians; dietetic competency trainingand credentialing, communication strategy, development ofprescribing and administering procedures; and ward education.Dietetic prescribing privileges were granted, implemented, andevaluation of this change in dietetic practice undertaken. Inconclusion, application of Lean Methodology enabled dietitians toclearly examine, in a systematic manner, delays, risks andinefficiencies with our current process of ordering NSAM. It led toa plan of action to improve quality of care to our patients, includingrenal patients, and reduce waste in our health care setting by timelyand appropriate commencement of NSAM.